(untitled) (International Journal of Engineering and Computer Science, 2015)
Nowadays Onboard Image compression algorithm has its own place in all the satellites sent to space for various applications. The images that are obtained by satellites are of huge volume, there arises the need for storing the images onboard. Onboard Image compression is an efficient technique used to reduce the size of an image so that the amount of data stored in the onboard mass memory can be increased. The usage of image compression systems onboard reduces the power and downlink bandwidth required to transmit the image to the ground station. JPEG2000 is one of the most widely used image compression algorithm for observation satellites, due to its high compression ratio. In this paper the performance of JPEG2000 algorithm is analyzed for various wavelet families. The performance of the algorithm is evaluated using the peak signal to noise ratio (PSNR) of the reconstructed image.